A Generalized Computer Technique for Solving Unconstrained Non-Linear Programming Problems (Dhaka University Journal of Science, 2013)
An unconstrained problem with nonlinear objective function has many applications. This is often viewed as a discipline in and of itself. In this paper, we develop a computer technique for solving nonlinear unconstrained problems in a single framework incorporating with Golden section, Gradient Search method. For this, we first combine this algorithm and then develop a generalized computer technique using the programming language MATHEMATICA. We demonstrate our computer technique with a number of numerical examples. Dhaka Univ. J. Sci. 61(1): 75-80, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15100